Species Compotition of Foraminifera Benthos in The Intertidal Coastal Water Of Klui Beach North Lombok - Laila Nurul Safitri; Imam Bachtiar; Lalu Japa; Muchlis (Jurnal Biologi Tropis, 2023)
Foraminifera can be utilized as a sign of ecological changes, so it is vital in the administration of coral reefs. The purpose of this study was to determine: the species composition of benthos foraminifera, substrate cover of habitat and diversity index, uniformity index, and dominance index species of benthos foraminifera. The method used in this research was systematic sampling, where the sample was systematically taken by making three pairs of squares on each transect so that 18 points were obtained, or 2700 samples. The four identified species of foraminifera namely: Sphaerogypsina globulus, Schlumbergerella neotetraedra, Schlumbergerella floresiana, and Baculogypsina sphaerulata with a comparative abundance of 1611, 775, 275, and 39 respectively. The highest species composition (59.5%) was S. globulus, followed by S. neotetraedra at 28.5%, S. floresiana at 10.1%, and the lowest was B. sphaerulata at 1.5%. At Klui Beach, the species diversity index of foraminifera was 0.960; the evenness index was 0.003; and the species dominance index was 0.448. The most substrate cover was limestone, among the six types of substrate cover. Large algae and live coral substrates were the only substrate covers that showed a significant correlation with the abundance of S. floresiana.